ANALISIS PENGARUH INFRASTRUKTUR TERHADAP KETIMPANGAN DISTRIBUSI PENDAPATAN KABUPATEN/KOTA DI PROVINSI BALI - I Nyoman Santika; I Gusti Agung Ayu Apsari Anandari (Adisam Publisher, 2025)
Income inequality remains a major challenge in Bali Province, despite the region’s heavy reliance on the tourism sector. Access to basic infrastructure such as electricity, roads, and clean water plays a crucial role in improving welfare and reducing disparities between regions. However, previous studies have shown significant inconsistencies regarding the impact of infrastructure on income inequality. Moreover, comprehensive research analyzing the simultaneous and partial effects of electricity, road, and water infrastructure on income inequality at the regency/city level in Bali remains limited. This study aims to analyze the influence of infrastructure variables (electricity, roads, and clean water) on income inequality across regencies/cities in Bali during the period from 2017 to 2023. The analysis employs panel data regression using Pooled OLS, Fixed Effects Model, and Random Effects Model approaches. Model selection is based on the Chow test, Hausman test, and Lagrange Multiplier test, incorporating both descriptive and inferential statistical techniques. The findings reveal that, simultaneously, infrastructure variables significantly influence income inequality, with an adjusted R-squared value of 0.937. Partially, electricity infrastructure has a positive and significant effect, indicating that increased access to electricity may be associated with rising inequality due to uneven economic activity. Road infrastructure exerts a significant negative effect, suggesting that improved road quality can help reduce inequality. Meanwhile, clean water infrastructure shows a negative but statistically insignificant effect. These findings highlight the importance of equitable and targeted infrastructure development—particularly in the electricity and road sectors—to effectively reduce income inequality in Bali through more inclusive and sustainable development planning.